Pelatihan Kepemimpinan dalam Kegiatan Organisasi Kemahasiswaan - Qonita Muslikhatun Amalia; Wahyu Eko Pujianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This community service initiative aims to enhance leadership skills among members of the organization, while also providing educational insights into the specific roles each member plays in advancing the Hima Management Study Program at Nahdlatul Ulama University Sidoarjo. The intended recipients of this program are the leaders and members of the Hima Management Study Program at Nahdlatul Ulama University Sidoarjo, totaling 30 participants. The methodology employed for this initiative involves a training approach that integrates educational components with interactive discussions. The outcomes of this initiative significantly contribute to fortifying the leadership acumen of both leaders and members within the Hima Prodi organization. This enhancement empowers them to effectively fulfill their roles and responsibilities, thereby upholding the organization's mission.